ANALISIS BELANJA PEMERINTAH KOTA PEKANBARU PADA KANTOR SATUAN POLISI PAMONG PRAJA - Sutra, Tessa Prima (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Pekanbaru City Government Expenditure Analysis Unit in the Office of the CivilService. This study aims to analyze the process of drafting the budget (RKA) and the allocationof development budget and actual expenditures in municipal police office Pekanbaru. The informantsis the Chief Financial Officer Pekanbaru City Government Secretariat and Head of Sub-Division of Finance Office of Pekanbaru City municipal police. The data collection technique isdocumentation and interviews. Data analysis techniques used measure of efficiency. Results ofresearch on pattern budgeting menunjuknn that still use the old method although there has beenan increase in status echelon head office. Budget and expenditure analysis Office of the municipalpolice in 2014 increased nearly 100% from 2012. As for the analysis of Actual Expenditure inmunicipal police offices with total regional expenditure in 2012 and 2014 amounted to 0.73%and 0.93%.